Habituasi Mujahadah Dalam Pembentukan Karakter Santri Di Blok Syauquna Al-Qur’an PPTQ Al-Asy’ariyyah, Kalibeber, Wonosobo - Happy Nurhidayah Putri Pamungkas; Mukromin Mukromin; Faisal Kamal (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
In language, habituation means habituation, which is what every human being experiences in carrying out the wheel of life. A good habit will certainly produce a good person too. In the teachings of the Islamic religion, we are encouraged to always worship and pray to Allah SWT so that we as His servants will receive blessings in living our lives in this world. One of the many forms of worship and prayer to Allah SWT is Mujahadah. Mujahadah itself comes from the Arabic word "jahada" which means sincere or serious. In terms of meaning, Mujahadah means being serious about fighting lust, both in terms of dhohir and inner self. Islamic boarding school life is never free from all forms of practices that become routine activities when studying at Islamic boarding schools, including mujahadah. The Tahfidzul Qur'an Al Asy'ariyyah Kalibeber Islamic Boarding School, Mojotengah, Wonosobo is one of the Islamic Boarding Schools that makes mujahadah a routine activity every week. With this routine mujahadah activity, it is hoped that the students can change their character in a dhohir manner to become individuals who are increasingly obedient in worshiping Allah SWT.